SEED AND POLLEN TTRANSMISSION OF A NEW UNIDENTIFIED MOTTLE DISORDER OF MAIZE IN INDONESIA - W. Wakman; D.S. Teakle; R. Louie (Indonesian Journal of Agricultural Science, 2000)
A new unidentified mottle disorder of maize Indonesia was found at the Research Institute for Maize and Other Cereals (RIMOC), Maros, South Sulawesi in 1995. Attempts to identify the disorder were made by mechanical inoculation, insect vector (Rhopalosiphum maidis and Peregrinus maidis) transmission, seed and pollen transmission, electron microscopy, and serological test. Fifty seeds from each of 22 ears of Arjuna maize plants showing the disorder were planted and symptoms on the seedlings were recorder at 1, 2, and 3 weeks after planting. The percentage of seedlings showing the disorder ranged from 40 to 100. Pollen of affected Arjuna was then used to pollinate four sweet corn female flowers. Hybrid seeds (50 per ear) of the crosses were planted and symptoms were recorded at 1, 2, and 3 weeks after planting. The results showed that percentage of seedlings showing the disorder ranged from 22 to 84. Electron microscopy and ELISA tests on 15 viruses and one phytospiroplasma antiserum however, gave negative results. Therefore, maize disorder at Maros was not identical to any known viral disease of maize. It could be a genetical disorder and has been given the name maize mottle.